Virtual Reality-Based Learning about "Animals Recognition" and Its Influence on Students' Understanding - Fatma Sukmawati; Eka Budhi Santosa; Triana Rejekiningsih (JTP - Jurnal Teknologi Pendidikan, 2023)
The development of Educational technology has experienced a rapid increase which has consciously contributed positively to the motivation for learning achievement, as well as virtual reality media which can bring reality into learning activities. The aim of this research is to produce virtual reality media for learning to know animal’ diversity. This research type is Research and Development with the ADDIE’ developing model which consists 5 steps : 1. Analysis, 2. Design, 3. Development, 4. Impelmentation, 5. Evaluation. The research subject consists of media experts, material experts, teachers, and 27 elementary school second-grade students. Data collection techniques consist of tests and non-tests, with interview guidelines, questionnaires, and test instruments for data analysis tailored to each instrument using average, descriptive, and n-gain. Research results show that Virtual Reality products are declared suitable for use as learning media and are effective in increasing students' understanding of animal introduction for elementary school students. The results of assessments by media experts, material experts, and teachers also showed that these media belong to the category of "appropriate" to be used as learning media. In addition, the media is also included in the "effective" category to help students understand material about animal recognition based on n-gain analysis.